2024
DOI: 10.1146/annurev-biochem-092823-113814
|View full text |Cite
|
Sign up to set email alerts
|

The Bis(monoacylglycero)-phosphate Hypothesis: From Lysosomal Function to Therapeutic Avenues

Uche N. Medoh,
Monther Abu-Remaileh

Abstract: Lysosomes catabolize and recycle lipids and other biological molecules to maintain cellular homeostasis in diverse nutrient environments. Lysosomal lipid catabolism relies on the stimulatory activity of bis(monoacylglycero)phosphate (BMP), an enigmatic lipid whose levels are altered across myriad lysosome-associated diseases. Here, we review the discovery of BMP over half a century ago and its structural properties that facilitate the activation of lipid hydrolases and recruitment of their coactivators. We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 111 publications
2
5
0
Order By: Relevance
“…Importantly, we found that genetic depletion of PLA2G15 strongly ameliorates neurodegeneration and liver damage leading to increased survival of NPC1-deficient mouse model [44][45][46][47] . These data suggest that inhibiting PLA2G15 represents a potential therapeutic strategy to boost BMP levels and treat multiple lysosome-related diseases, an observation consistent with the BMP therapeutic hypothesis 1 .…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Importantly, we found that genetic depletion of PLA2G15 strongly ameliorates neurodegeneration and liver damage leading to increased survival of NPC1-deficient mouse model [44][45][46][47] . These data suggest that inhibiting PLA2G15 represents a potential therapeutic strategy to boost BMP levels and treat multiple lysosome-related diseases, an observation consistent with the BMP therapeutic hypothesis 1 .…”
Section: Discussionsupporting
confidence: 70%
“…We speculate that BMP stability is maintained by an unidentified biological machinery that protects its 2,2' BMP isoform from acyl migration 1 . Future studies should investigate the preferential synthesis or preservation of 2,2' BMP, as well as the enzymes or processes required for its conversion to the 3,3' isoform during its catabolism.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations